Isolation and structural characterization of monomeric and dimeric forms of replicative intermediates of Kilham rat virus DNA. - Gunther, M (1976)
Two virus-specific species of newly synthesized DNA were isolated from rat fibroblast cell cultures infected with the Kilham rat virus (RV). These two DNA species were purified; their behavior on hydroxyapatite chromatography and their sedimentation coefficients in sucrose gradients were determined. One of the two species corresponds to the linear double-stranded form of the RV DNA, and the other corresponds to the dimeric duplex form. After denaturation, a fraction of both species showed an intramolecular renaturation; these molecules are composed of viral strand covalently linked to complementary strand. Models for the structure of both species are posposed. Both species may be considered as double-strand replicative intermediates of the single-stranded RV DNA.